Managers with and without Style: Evidence Using Exogenous Variation - Fee, C. Edward; Hadlock, Charles J.; Pierce, Joshua R. (Review of Financial Studies, 2013)
In a large panel of Compustat firms, we find that firm policy changes after exogenous CEO departures do not display abnormally high levels of variability, casting doubt on the presence of idiosyncratic-style effects in policy choices. After endogenous CEO departures, we do detect abnormally large policy changes. These changes are larger when the firm is likely to draw from a deeper pool of replacement CEO candidates, suggesting the presence of causal-style effects that are anticipated by the board. Our evidence suggests that managerial styles are not transferred across employers and that standard F-tests are inappropriate for identifying style effects.